Gut microbiome characteristics of comorbid generalized anxiety disorder and functional gastrointestinal disease: Correlation with alexithymia and personality traits - Guo, Xunyi; Lin, Feng; Yang, Fengjiao; Chen, Jing; Cai, Weixiong; Zou, Tao (Frontiers in Psychiatry, 2022)
Objective：To investigate the characteristics of intestinal flora in patients with functional gastroenteropathy and generalized anxiety disorder and the relationship between intestinal flora and psychological factors. Methods: From March 2020 to December 2020, a total of 35 patients with functional gastroenteropathy and generalized anxiety disorder, 30 healthy controls, 16 patients with functional gastroenteropathy and 44 patients with generalized anxiety disorder were selected from the Affiliated Hospital of Guizhou Medical University. Fecal samples were collected from each group, and the related psychophysiological factors scales (Hamilton Anxiety Scale, Hamilton Depression Scale, Neurotic personality Questionnaire, concept of illness questionnaire, Toronto Alexithymia Scale, severity of physical symptoms Scale, cognitive emotion regulation questionnaire) were improved. 16S rRNA high-pass sequencing was used to determine the correlation between intestinal flora changes and functional gastroenteropathy with generalized anxiety disorder. Then the scale and gut microbiota results were analyzed for correlation to determine the correlation between personality traits and gut microbiota. Results: We found similar intestinal microbiota in patients with functional gastroenterology, generalized anxiety disorder, and functional gastroenteropathy with generalized anxiety disorder. but the relative abundance of Clostridium was significantly increased in patients with functional gastrointestinal disease and generalized anxiety. The relative abundance of Haemophilus influenzae was significantly increased in patients with functional gastrointestinal disease without generalized anxiety disorder. Intestinal microecological composition was significantly correlated with personality traits. Conclusion: FGIDS comorbidity GAD may be related to the increase of relative abundance of Fusobacterium. FGIDS non-comorbidity GAD may be related to the increased relative abundance of Hemophilus. The increased relative abundance of Fusobacterium and Megamonas is associated with personality traits such as affective recognition and expression disorder, neuroticism and negative cognition of disease.